2001
DOI: 10.1007/bf03028306
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative medical management and outcome following thymectomy for myasthenia gravis

Abstract: Our data show that the severity of MG failed to predict the need for postoperative ventilation. A combined anesthetic technique was a safe and cost-effective alternative to balanced anesthesia as it provided optimal operating conditions and resulted in fewer admissions in ICU and shorter hospital stays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 29 publications
0
18
0
2
Order By: Relevance
“…It is a subject of debate if the determinants of postoperative mechanical ventilation are the preoperative clinical condition (such as Osserman's class), 18 or the intraoperative use of muscle relaxants. 2 In our series, none of the seven Osserman class III patients suffered from respiratory complications.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…It is a subject of debate if the determinants of postoperative mechanical ventilation are the preoperative clinical condition (such as Osserman's class), 18 or the intraoperative use of muscle relaxants. 2 In our series, none of the seven Osserman class III patients suffered from respiratory complications.…”
Section: Discussionmentioning
confidence: 51%
“…The use of muscle-relaxants in patients with MG has been associated with a higher rate of unsuccessful extubation at the end of surgery and with longer postoperative mechanical ventilation and hospital stay. 2,5 We avoided muscle relaxants in myasthenic patients because the neuromuscular effects of non-depolarizing muscle relaxants are known to be prolonged in patients with MG. 1 The speed of onset of neuromuscular block is accelerated, the degree of block is potentiated and the rate of recovery is decreased. 6 Chevalley et al described the evolution of the perioperative management of myasthenic patients undergoing thymectomy and the possibility to predict the need for systematic postoperative ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 One study indicated that anesthesia with desflurane combined with remifentanil is safe in patients with MG. 15 Although general anesthetics may affect neuromuscular transmission, recent anesthetic approaches may be safely performed in myasthenic patients. [16][17][18][19][20][21] Our patient was adequately monitored, and no abnormal signs were seen during surgery. She had no immediate adverse effects from the anesthetics.…”
Section: Discussionmentioning
confidence: 99%